Cenpj/CPAP regulates progenitor divisions and neuronal migration in the cerebral cortex downstream of Ascl1 - Garcez, Patricia P. (Nat Commun, 2015)
The proneural factor Ascl1 controls multiple steps of neurogenesis in the embryonic brain, including progenitor division and neuronal migration. Here we show that Cenpj, also known as CPAP, a microcephaly gene, is a transcriptional target of Ascl1 in the embryonic cerebral cortex. We have characterized the role of Cenpj during cortical development by in utero electroporation knockdown and found that silencing Cenpj in the ventricular zone disrupts centrosome biogenesis and randomizes the cleavage plane orientation of radial glia progenitors. Moreover, we show that downregulation of Cenpj in post-mitotic neurons increases stable microtubules and leads to slower neuronal migration, abnormal centrosome position and aberrant neuronal morphology. Moreover, rescue experiments shows that Cenpj mediates the role of Ascl1 in centrosome biogenesis in progenitor cells and in microtubule dynamics in migrating neurons. These data provide insights into genetic pathways controlling cortical development and primary microcephaly observed in humans with mutations in Cenpj.